Looking at France - Powell, Jillian (Milwaukee, WI Gareth Stevens Publishing, 2007)
Millions of people from other countries visit France every year. Readers will see the busy city of Paris, the amazing Eiffel Tower, the majestic Notre Dame cathedral, snowy mountains, and sunny beaches. Learn about life in France, from foods to fashions and from Bretons to boules.
Elementary
Keywords: France; France - Social life and customs